2015
DOI: 10.11604/pamj.2015.20.251.5429
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of persistent microalbuminuria and associated factors among hiv infected children attending a Tertiary Hospital in Northern Tanzania: a cross sectional, analytical study

Abstract: IntroductionHuman Immunodeficiency Virus (HIV) infection is a significant cause of paediatric morbidity and mortality especially in Sub-Saharan Africa. It affects the kidney by injuring the glomerular and tubular epithelial cells causing leakage of albumin in urine. Microalbuminuria is known to be an early indicator of kidney injury including HIVAN. The purpose of this study was to identify the prevalence and factors associated with microalbuminuria among HIV infected children receiving care and treatment at K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…This high prevalence of microalbuminuria highlights the magnitude of early renal dysfunction in HIV-infected patients before ART initiation. This was different from most of the studies conducted in recent times [5][6][7][8][9][10][11][12][13].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This high prevalence of microalbuminuria highlights the magnitude of early renal dysfunction in HIV-infected patients before ART initiation. This was different from most of the studies conducted in recent times [5][6][7][8][9][10][11][12][13].…”
Section: Discussioncontrasting
confidence: 80%
“…Higher prevalence of microalbuminuria found in other areas of SSA; in South Africa the prevalence of microalbuminuria was found to be 24.0% [9], however, they included in-patients who have been reported to be at higher risk of microalbuminuria due to advanced HIV [14] compared to our study participants who were outpatients. Another study in Tanzania demonstrated that advanced HIV disease was significantly associated with microalbuminuria at 28.8%, however, they included patients who were already on ART [12]. The only study done in Africa that looked at participants with similar characteristics (adult HIV ART naïve patients attending an outpatient clinic was in Tanzania demonstrated the highest recorded microalbuminuria at 70.2% [13].…”
Section: Discussionmentioning
confidence: 99%
“…This study looked at HIV − infected ART naïve patients attending the Mulago ISS clinic and the prevalence of microalbuminuria reported was different from most of the studies conducted in recent times [5,6,[8][9][10][11][12][13][14]. It was challenging to compare this study with those conducted earlier due to several factors which include differing study participants and sample sizes, in addition to varying assay techniques and methodologies.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, to decrease the risk of emerging ESRD, early screening and treatment of microalbuminuria is required, especially for those at high risk (advanced HIV disease and those with a CD4 count below 350 cells/µL). Urinary albumin screening can be done in a situation where routine screening for microalbuminuria is not available [ 21 ].…”
Section: Presentation Of Hiv Nephropathy In Africamentioning
confidence: 99%